AGRIBUSINESS DEVELOPMENT FOR FARMING RICE ON PROGRAM CONCERN TO FARMER FOOD SECURITY AT BOALEMO REGENCY - Masruroh, Eni (Jambura Agribusiness Journal, 2021)
The research aims to develop an alternative recommendation agribusiness program development paddy rice farming relation to food security in the district was. This research is quantitative. Sources of data in this research is secondary data and primary data from questionnaires. The data analysis technique used is the SWOT analysis. These results indicate that Based on the SWOT analysis proves that the strategy of the development of barns through agribusiness development program to support rice farming rice fields of food security in the district was located in quadrant I, which means it supports aggressive strategy or strategies SO. In quadrant I (aggressive) all the potential power that the majority of the district was a farmer who has the experience and motivation of farming is high, the potential for a large area, the production ability is above average, and institutional barns that support, can utilize / seize opportunities demand for rice increases, as well as increased yield harvest with agricultural intensification, so the chances of barns society has the potential to be developed further.